2022
DOI: 10.3390/foods11111587
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anthracophyllum discolor and Stereum hirsutum as a Suitable Strategy for Delignification and Phenolic Removal of Olive Mill Solid Waste

Abstract: This study evaluated the use of the white-rot fungi (WRF) Anthracophyllum discolor and Stereum hirsutum as a biological pretreatment for olive mill solid mill waste (OMSW). The WRF strains proposed were added directly to OMSW. The assays consisted of determining the need to add supplementary nutrients, an exogenous carbon source or use agitation systems, and evaluating WRF growth, enzyme activity, phenolic compound removal and lignin degradation. The highest ligninolytic enzyme activity was found at day 10, re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
(105 reference statements)
3
7
0
Order By: Relevance
“…Different parameters were characterized for untreated grape pomace and treated grape pomace, including analysis for liquid and solid phase obtained after hydrothermal treatment. Total solids (TS), volatile solids (VS), and soluble chemical oxygen demand (sCOD) were measured according to standard methods (30). In addition, lignin content was measured for OMSW, using the Klason lignin method (TAPPI T 222 om-02) [28].…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Different parameters were characterized for untreated grape pomace and treated grape pomace, including analysis for liquid and solid phase obtained after hydrothermal treatment. Total solids (TS), volatile solids (VS), and soluble chemical oxygen demand (sCOD) were measured according to standard methods (30). In addition, lignin content was measured for OMSW, using the Klason lignin method (TAPPI T 222 om-02) [28].…”
Section: Chemical Analysismentioning
confidence: 99%
“…The mixture was stirred for 1 min in a vortex apparatus and centrifuged at 1200 G for 10 min. The methanol layer was separated, and the extraction was repeated four times [30]. To determine the antioxidant capacity in the liquid phase, the antiradical activity (2,2-diphenyl-1-picrylhydrazyl (DPPH) was measured, the DPPH analysis was done measuring the variation in absorbance at 515 nm after 30 min of reaction with the radical DPPH, using Thermo Scienti c's UV-Vis Orion AquaMate 8000 spectrophotometer.…”
Section: Chemical Analysismentioning
confidence: 99%
“…discolor was isolated from decaying wood in the rainforests of southern Chile. The culture was cultivated in Petri dishes (94 × 16 mm) at 25 • C for 7 days in a medium consisting of 39 g L −1 Potato Dextrose Agar (PDA) sterilized at 121 • C for 20 min [20].…”
Section: Fungal Strain and Inoculum Preparationmentioning
confidence: 99%
“…Additionally, the OMSW contained 61.5% water and 38.5% total solids, which makes it highly viscous, limiting the liquid phase used to recover ligninolytic enzymes. In this sense, Benavides et al [20] used water to recover ligninolytic enzymes and concluded that it is necessary to use other liquid sources to recover enzymes in the pre-treatment of OMSW with A. discolor. Thus, the addition of AS should have high nitrogen content and high water content to generate a liquid phase for recovery of enzyme extracts.…”
Section: Characterization Of Olive Mill Solid Waste and Aquaculture S...mentioning
confidence: 99%
See 1 more Smart Citation